Histopathological Profile Of Cervical Biopsies In Sarawak - Madzlifah, Ahadon; Arlizan Baizura, Ariffin; Aini Afiqah, Gas @ Mohammad Hafiz; Peter Wong, Qin Chai; Mimi Azira, Ahmad Zaidil; Tharseni V., Parimalam; Awi, Idi (Malaysian Journal of Pathology, 2023)
Introduction: Cervical cancer is the third most prevalent cancer in women in Malaysia. Managing the disease has placed a significant economic burden of approximately RM312 million on the government each year. This study aimed to evaluate the pattern of the histopathological profile of cervical biopsies and to determine the association of risk factors with the findings of the cervical biopsies performed at Klinik Sakit Puan & Infertiliti Universiti Malaysia Sarawak (UNIMAS). Materials & Methods: This retrospective study was conducted in a specialist clinic in UNIMAS from January - August 2023. Data regarding the patients and the cervical biopsy findings were recorded using a pre-designed form and were analysed using Statistical Package for Social Sciences version 28.0. Results: The most common finding observed was chronic cervicitis (20.9%), whereas cervical intraepithelial neoplasia (CIN) lesions were observed in 20.4% of cases. Among the CIN findings, 87.23% were classified as CIN I, while CIN II and CIN III accounted for 8.51% and 4.26%, respectively. Additionally, 6.38% of the overall CIN findings were associated with HPV. However, there was no significant association between the patient’s age and the cervical biopsy finding (p>0.05). Discussion: Our study did not observe any significant association between age or ethnicity and the cervical biopsy finding. This study highlights the importance of other sociodemographic data regarding cervical cancer, which should be obtained from all patients referred for a cervical biopsy, as this information is relevant to most healthcare interventions in terms of improving the morbidity and mortality associated with cervical cancer.